2011
DOI: 10.1590/s1807-59322011000800021
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic dynamics of cartilage explants over a long-term culture period

Abstract: INTRODUCTION:Although previous studies have been performed on cartilage explant cultures, the generalized dynamics of cartilage metabolism after extraction from the host are still poorly understood due to differences in the experimental setups across studies, which in turn prevent building a complete picture. METHODS:In this study, we investigated the response of cartilage to the trauma sustained during extraction and determined the time needed for the cartilage to stabilize. Explants were extracted asepticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Gene expression of cartilage relevant ECM marker genes like collagen II and aggrecan stayed relatively stable for 14 days before abruptly decreasing. Similar genetic dynamics have been observed beforehand in explant culture models which used immobilized, 6-mm-diameter bovine cartilage discs (25). These results indicate, that osteochondral live slices do not additional treatment like immobilization in agarose or strong perfusion pressures for nutrition and retaining their tissue speci c genetic phenotype -effectively reducing the handling necessities by a great deal.…”
Section: Discussionsupporting
confidence: 74%
“…Gene expression of cartilage relevant ECM marker genes like collagen II and aggrecan stayed relatively stable for 14 days before abruptly decreasing. Similar genetic dynamics have been observed beforehand in explant culture models which used immobilized, 6-mm-diameter bovine cartilage discs (25). These results indicate, that osteochondral live slices do not additional treatment like immobilization in agarose or strong perfusion pressures for nutrition and retaining their tissue speci c genetic phenotype -effectively reducing the handling necessities by a great deal.…”
Section: Discussionsupporting
confidence: 74%
“…It is quite difficult to control the response from individual samples. However, this model more closely represents the physiological environment than does the monolayer culture model and this model minimizes the presence of the complicated systems found in the animal model study [18, 19]. The experiment of this study was designed to mimic the microenvironment surrounding the inflammatory joint found in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, animal experiments have a serious limitation due to the differences in biological responses; this is due to the differences between species. Furthermore, the model is made even more difficult because of the complicated biological systems involved as revealed in in vivo studies [18, 19]. In order to avoid such systemic and environmental complications in the animal model, the cartilage explant culture model has been used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we hypothesized that the paracrine chondroprotective effects of ASC on the OA cartilage would be advantageous due to the recovery of MMP/TIMP homeostasis. To avoid the dedifferentiation of chondrocytes, cultured in monolayer, or the synthesis of cartilage extracellular matrix (ECM) de novo in pellet cultures, we have chosen a model of human OA cartilage explants (CE), containing viable cells, readily surrounded by native OA cartilage ECM environment [ 10 ]. CE were cocultured or not with ASC, and the alterations in MMP and TIMP secretion by CE in response to ASC cocultures were analysed.…”
Section: Introductionmentioning
confidence: 99%